The impact of infant mortality on societal happiness - Davis, Song (My University, 2026)
Happiness has come to be seen as a valuable tool to measure the impact of societal changes. In this study, the issue of infant mortality is examined to assess its impact on societal happiness. Using a cross-sectional regression model, the impact of reducing the infant mortality rate on societal happiness is examined for more than 100 of the world’s nations in the most recent year for which data is available, 2023. This is done first because research has demonstrated that infant mortality strongly impacts the individual happiness of those directly impacted. It is also because there is a long history of infant mortality rates being used in the research literature as a pathway to understand the level of deprivation within a nation. For these reasons, assessing whether reductions in infant mortality yield significant positive returns on societal happiness should help clarify whether eradicating poverty, increasing access to health resources, or lessening issues of malnutrition are actions that increase the happiness level of not just the individuals directly impacted but the overall level of happiness within nations. Results show that increases in the infant mortality rate do not significantly decrease societal happiness. This shows that this study’s research hypothesis that nations with lower rates of infant mortality have higher levels of societal happiness should be rejected. This study, however, finds that a $1,000 increase in per-capita GDP for nations with a median level of per-capita GDP ($4,790) significantly increases (p < .01) the societal happiness of citizens of those nations (+0.576 points). This alternate finding suggests that per-capita GDP, which is a different proxy for deprivation, may be an even stronger tool for researchers when examining deprivation and its impacts. It also provides evidence that governments could increase the happiness of their citizens by reducing deprivation levels.
Keywords: Happiness; Deprivation; Infant mortality